The Clinical Efficacy of Three Different Follicle-Stimulating Hormones for Follicle Growth and Development in Long-Protocol Controlled Ovarian Hyperstimulation Treatment - Zhang XQ; Zhang LJ; Zhu XL; Xu H; Luo YQ; Yao L; Huang QW; Nong YQ; Liu WJ; Liu FH (Drug Design, Development and Therapy, 2021)
Xi-Qian Zhang,* Li-Jia Zhang,* Xiu-Lan Zhu, Hong Xu, Yan-Qun Luo, Li Yao, Qian-Wen Huang, Ying-Qi Nong, Wen-Juan Liu, Feng-Hua Liu Reproductive Medical Center, Guangdong Women and Children Hospital, Guangzhou, 511442, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng-Hua LiuDepartment of Reproductive Medical Center, Guangdong Women and Children Hospital, No. 521 Xingnan Road, Panyu District, Guangzhou, 511442, Guangdong Province, People’s Republic of ChinaTel +86 20-3915 1861Fax +86 20-3915 1617Email liufenghua377@21cn.comObjective: To compare the use and clinical efficacy of three different follicle-stimulating hormones (FSHs) for follicle growth and development in long-protocol controlled ovarian hyperstimulation (COH).Methods: A total of 540 gonadotropin-releasing hormone (GnRH) agonists’ long protocol treatment cycles at our hospital between January 2015 and May 2020 and met the inclusion criteria were retrospectively analyzed. The cycles were divided into three groups based on their indexes (groups A, B, and C). Each of the groups received a different type of FSH during treatment. A cross-group comparison was then undertaken to evaluate the growth and development of the three largest follicles and the patients’ pregnancy-related indexes between the normal-response and high-response populations.Results: In the normal-response populations, the number of high-quality embryos obtained in groups A and B was significantly higher than in group C, and the FSH dosage was significantly lower than in group C (P < 0.05). There were more follicles with a diameter of 16– 18 mm found in group A than in group C on the day of hCG injection (hCG day) (P < 0.05), but there were no significant differences in the groups in other indicators. In the high-response populations, the number of oocytes retrieved and high-quality embryos obtained in group A were significantly higher than in group C (P < 0.05), and the total dosage and duration of FSH stimulation in group C were significantly higher than groups A and B (P < 0.05).Conclusion: Three different types of FSH led to comparable growth rates of the three largest follicles and clinical pregnancy rates per fresh cycle in long-protocol COH treatment.Keywords: follicle-stimulating hormone, follicle growth rate, high-quality embryos, Gn stimulation duration, follicle distribution on hCG day